Advances in Differential and Difference Equations and Their Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue presents a collection of articles that highlight the significant progress in the study of differential and difference equations. These contributions cover a wide range of topics, from boundary value problems and the asymptotic behavior of solutions to complex mathematical models and the application of fractional and difference equations in various scientific and engineering fields. Differential equations are a core mathematical tool for modeling dynamic systems in a diverse range of areas, such as physics, biology, economics, and engineering. Likewise, difference equations provide discrete counterparts to continuous models, which are crucial in understanding phenomena occurring in digital systems and various computational models. The papers presented in this Special Issue reflect the latest theoretical advancements and applications in these important research areas.